MANAJEMEN KARIER SUMBER DAYA MANUSIA - I Gusti Bagus Wiksuana (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2007)
Career development is viewed as long term training and is broader than just job skill training. It is argued that attention on employee career development is not need to be holistic, because it will not useful for both individuals and the organization. Strategy which can be implemented is dual career path in life time employment framework. Based on such a strategy, in his/her career cycle, individual in organization will go through two career paths i.e., non ?structural or functional (expertise seniority) and structural (function in organization structure) paths. Dual career path is needed as a way out of channel narrowness to the upper management level, whereas life time employment framework is needed to guarantee employee?s future career in organization